Importance of Manpower Training to Enhance Productivity of Staff Performance - Akanbi, Felicia Kehinde; Adetunji, Adeniyi Temitope (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The importance of training and development, and the growing complexity of the work environment in present day society, cannot be over emphasized. Training and development ensure that organizational staff possess the knowledge and skills needed to perform their jobs effectively and adapt to ever changing technology. This paper uses desk research to evaluate work carried out related to training and manpower development, especially debate centered on how to improve the quality of staff performance. The study finds that, although a host of workshops, seminars and training are available, few are assessed due to the differences between budgetary provisions and actual funds released, for various years, at both federal and state levels.